Studies on Schismatoglottideae (Araceae) of Borneo XXVIII – A New Bakoa from Indonesian Borneo - Wong Sin, Yeng (International Aroid Society Inc., 2013)
Bakoa sicula S.Y.Wong, is described and illustrated from Cretaceous granites of Kalimantan Barat, Indonesian Borneo. A key to the four described Bakoa species is provided.